IT-Based Media in Mathematics Learning in Elementary Schools - Ilham Syamsudin; Kusmiyati Arum Ningsih; Siti Rachmah; Rasilah Rasilah (Journal of Mathematics Instruction, Social Research and Opinion, 2024)
Technological developments are increasingly rapid; in this technological development, many interactive and effective learning media have emerged to be applied in learning. Using the literature study method, researchers want to convey learning media teachers can use or develop using current technology. Such as using the PowerPoint application to present lesson material. Digital Geoshape application to make it easier to study geometry material. GeoGebra application that can be used by students and teachers in line equation material. Adobe Animate application that can create or develop interactive learning media. Online-based PowToon media provides audiovisual media such as animated cartoons, etc. The Canva application provides presentation designs, etc., which help design learning media. Wordwall-based games are games that offer gameplay and learning features. And educational adventure games that can be used in fraction counting operation material.